The effects of balanced biliteracy on Greek-German bilingual children's secondary discourse ability. Issue 8 (13th September 2020) - Bongartz, Christiane; Torregrossa, Jacopo
ABSTRACT: Several studies have revealed the cognitive and linguistic benefits of balanced bilingualism, but the research on balanced biliteracy is still in its initial stages (Marinis et al. submitted. "Biliteracy Education Impacts on Cognition Selectively."). This study investigates the positive effects of balanced biliteracy on the development of secondary discourse ability involved in narrative production. The analysis is based on narratives told by 30 Greek-German bilingual children (9–12 years) in both their languages. The children are divided in three groups, differing in language proficiency in each respective language and features of the educational setting (in terms of balance of teaching hours dedicated to each language). The results reveal that the features of the educational setting are the most reliable predictor of children's narrative skills. Moreover, balanced biliteracy has the effect of evening out imbalances in language proficiency. The study contributes to identifying the factors that affect secondary discourse ability and motivate variation in the development of literacy skills (Francis 2006. "The Development of Secondary Discourse Ability and Metalinguistic Awareness in Second Language Learners." International Journal of Applied Linguistics 16 (1): 37–60; Bongartz 2016. "Bilingual and Second Language Development and Literacy – Emerging Perspectives on an Intimate Relationship." Proceedings of the 21st International Symposium of Theoretical and Applied Linguistics 2013, Thessaloniki, April 5–7, 2013).